Plasma desmosine, a biomarker of elastin degradation, predicts outcomes in coronary artery disease. (25th November 2020) - Iskandar, Z; Patel, S; Lancefield, T; Freeman, M; Horrigan, M; Farouque, O; Huang, J.T.J; Lang, C.C; Burrell, L.M; Choy, A.M
Abstract: Background: Recent evidence from animal studies suggests that elastin degradation accelerates atherosclerosis and increases risk of plaque rupture and subsequent myocardial infarction and stroke. Desmosine is an elastin-specific degradation product. We analysed the prognostic value of plasma desmosine (pDES) in a cohort of patients with coronary artery disease (CAD). Methods: Patients with CAD (n=400) undergoing elective coronary angiography were prospectively recruited over 3 years and had bloods drawn for analysis of pDES using a validated stable isotope dilution liquid chromatography-tandem mass spectrometry method. Patients were followed up for 12 months for major adverse cardiovascular events (MACE: composite of death, myocardial infarction, target vessel repeat revascularisation, target lesion revascularisation, and heart failure hospital admission). The upper limit of normal for pDES is 0.35 ng/mL. The predictive value of pDES for MACE was analysed with Cox-proportional hazards ratio (HR) model and Kaplan-Meier survival analysis. Results: During follow-up, there were 36 MACE events. Median pDES level across the entire cohort was 0.3 ng/mL (IQR 0.23–0.41 ng/mL). Patients with a pDES level >0.35 ng/mL were more likely to be male and older with a mean age of 69.7±10.3 years, have a history of prior stroke or transient ischaemic attack (TIA) and COPD. In univariable analysis, a pDES level of >0.35 ng/mL was associated with an increased risk of MACE (HR 4.76, 95% CI: 2.34–9.68, p<0.001). In multivariable analysis, pDES >0.35 ng/mL was associated with risk of MACE after adjustment for age, sex, COPD status and previous stroke and TIA (HR 3.97; 95% CI: 1.82–8.67, p=0.001) (Figure). Conclusion: Increased elastin degradation as measured by elevated pDES levels, predicts outcomes in patients with CAD independent of traditional cardiovascular risk factors and may play a role as a future biomarker in these patients. Funding Acknowledgement: Type of funding source: None